Marginal Returns in Small and Large Companies - Ronald F. Anderson; Gerald D. Newbould (Journal of Small Business Finance, 1991)
Previous studies of large versus small company performance, though frequent, have not produced a clear answer as to whether large companies outperform small companies or vice versa. This article highlights retentions - the fact that different companies have different dividend policies —as a problem in that retentions obscure accurate measurement of a company's growth. Retentions obscure accurate measurement in that these funds are not costed, hence a high retentions company is getting cost free funds using conventional accounting and security analysis techniques, and, thus other things equal, will outperform a low retentions company. The retentions problem can be overcome by a technique that produces a company statistic called “cash equivalents per share” (CEPS). When CEPS is calculated for 771 companies, arrayed into 13 SIC industrial classifications, each containing a portfolio of large companies (over 1 billion in 1988/1989 sales) and a portfolio of small companies (under 200 million in 1988/1989 sales), then in every industry, the portfolio of large companies outperforms the portfolio of small companies. An additional feature of CEPS covered in the study is that in a competitive economy, the CEPS should show a benchmark growth of zero. The 13 portfolios of large companies all show a CEPS growth rate in excess of zero; only three of the 13 small company portfolios do this. As this is an introductory and relatively small scale study, there are research opportunities to confirm or refute these initial findings.
Keywords: L25; G35; G12; G32; 650; Marginal Returns; Small Firm; Large Firm